Denial of Self: A Contrasting view on Transgender through Meredith Russo’s If I was Your Girl (International Journal of Food and Nutritional Sciences, 2022)
Meredith Russo, an American transgender novelist portrays a contrasting view on transgender in her novel If I was Your Girl. Transgender people have a different gender identity which was assigned during their birth. Russo talks about the denial not the regular social denial caused to them but about the self-denial they do to themselves. In the novel, the protagonist Amanda faces the gender identity crisis and strives hard to accept herself. Transgenders discriminate their self in the grounds of biological sex and face many criticisms and difficulties in their living. If they show their identity as a transgender in the society, families, and friends will illtreat them. They avoid telling their gender truth to stop the people in the society to see them as an untouchable one. Transgender should accept their identity as a part of human condition and understand it is the biology that determines their sex. They should accept themselves as strong and extraordinary.